Thematic Analysis Of Research Studies On Maqasid Shariah And Mental Health - Ulfah Mansurah Zainudin; Nurzahidah Jaapar; Fadhilah Adibah Ismail; Ghazali Jaapar; Hasnah Husiin (USIM Press, 2024)
VOL. 28 NO. 1 Page (45-57)